Answer:
• (x + 10)² + (y+6)² = 121
Explanation:
For this case we have the following expression:
![x^2 + y^2 +20 x + 12y +15=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ublmuy1qnu7zjegosz9087ecvg6p30mzes.png)
And we want to write this on this general way:
![(x-h)^2 +(y-k)^2 = r^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/796ewgjgarkp6zgskqnda6gub402e80voe.png)
So on this case we need to complete the squares like this:
![x^2 + 20 x + ((20)/(2))^2 + y^2 + 12y + ((12)/(2))^2 +15 =((20)/(2))^2+((12)/(2))^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/u4ql0pog6j3z413za3rgu8hyii75rdfzig.png)
Now we can subtract from both sides 15 and we got:
![(x^2 + 20 x +100) + (y^2 + 12y +36) = 100+36 - 15](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3vptiy8gzmwkldb8pvhk5i8exdhsdbhdra.png)
![(x+10)^2 +(y+6)^2 = 121](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d53a2viq93luu7ech5o25cce3cxg49u9d9.png)
And we can write the last expression like this:
![(x-(-10))^2 +(y-(-6))^2 = 121](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jhc8zwksyxvra4hcnve1xhbx1xisrdjv8p.png)
And if we compare to the general expression we see that:
![h = -10 , k = -6, r=√(121)=11](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8rimis6p905rwtlfjyxr874uta3q92b67u.png)
So the correct option for this case would be:
• (x + 10)² + (y+6)² = 121